Impact of Credit Risk Management on the Profitability of Commercial Banks in Nepal - Thapa, Sanju; Amgain, Pushpa Nidhi (Janaprakash Journal of Multidisciplinary Research, 2025)
This study aims to investigate the impact of credit risk management on profitability of commercial banks in Nepal. This study was based on descriptive and causal research design. Out of 20 commercial banks of Nepal, five banks were selected as samples using the lottery method. Secondary data were collected from the annual report to conduct this study from FY 2014/15 to FY 2023/24. The CDR, NPL and CAR serve as independent variables while return on assets (ROA) and earnings per share (EPS) are used as dependent variable in Nepali commercial banks. The regression results indicate that the coefficient of CAR is positive and rest of the NPL and CAR have negatively related with ROA under model I. Under the model II, coefficient of CDR, NPL and CAR are negatively related with EPS. The findings of the study reveal that there is a negative relationship between the credit deposit ratio and non performing loans with return on assets and earnings per share. The capital adequacy ratio does not have a significant effect on return on assets and earnings per share. Future research direction could be taking moderating variable such as size of the bank to define the impact of credit risk management on profitability of commercial bank in Nepal.